Prevalence and Determinants of Tobacco Use in the Undergraduate Students of Nursing in Peshawar, KP: Prevalence and Determinants of Tobacco Use - Munir, Bakht; Karim, Hassan; Rehman , Wahid ur; Bano, Nasim; Khadija Bibi; Saeed, Moneeda (Pakistan Journal of Health Sciences, 2023)
The plants of tobacco contain habit-forming chemical substances known as nicotine. Tobacco products are available in different forms like Smoke Tobacco (ST) and Smokeless tobacco (SLT). Common STs are cigarette, pipe tobacco (hookah), cigar, and e-cigarette. Objective: To find the prevalence and determinants of tobacco use among undergraduate nursing students. Methods: A quantitative, cross-sectional descriptive study was carried out among undergraduate nursing students. The convenient sampling technique was adopted. The sample size was calculated by Raosoft software with a known population of 1800, having a margin of error of 5%, a confidence interval of 95%, and a calculated sample size of 317. Results: Majority of the participants in this study were Male, out of total 317 participants, 135 (42.6%) of the participants, (male 51.4% and female 23.8% used tobacco) while 174 (54.9%) never tried to use tobacco. Among the tobacco users (135)25.9% smoked tobacco only (male, 31.6%: female, 14.3%), 4.1% used naswar only (male, 6.1%: female, 0%), and 5.4% (male, 6.6%: female, 1.9%) of the participants used both cigarette and naswar, and 6.9% (male, 7.1: 6.7%) of the participants used other forms of tobacco products. Conclusions: In conclusion, it was found that tobacco use among nursing students of different colleges in Peshawar is common. Male students are more prone to become users because of family members, friends and college fellows’ behaviors. Most of them tried in the age of 10 to 20 years.